« J’étais pas vraiment moi » - Camille Lancelevée; Caroline Protais (Anthropologie & Santé)
The penal principle of “mental disorder defense” has been at the center of a major controversy among French psychiatrists since the 1980’s. This article aims at apprehending the “insanity defense” from the point of view of those being subjected to this measure. The fifteen interviews conducted with hospitalized patients highlight different ways of experiencing this measure and the resulting hospitalization. Some patients find in the psychiatric diagnosis a new guideline for their biographical narrative and experience the hospitalization as a moment of necessary biographical bifurcation. Others refuse the clinical diagnosis, considering it as groundless in their eyes. The penal measure is hence regarded as an unfair decision and the hospitalization as an arbitrary confinement. By highlighting these contrasted experiences of « penal irresponsibility », this article sheds another light on the controversy around this justice principle and contributes to a better understanding of patient’s subjectivity in psychiatry.